ROLE OF INTERNET OF THINGS (IOT) IN REVOLUTIONIZING DIGITAL MARKETING - Dhanawade , Murlidhar; Nikam, Poonam; Mane, Shivaji Tukaram (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper investigates the transformative influence of the Internet of Things (IoT) on digital marketing strategies. Through a comprehensive survey, the study explores the role of IoT in enhancing the effectiveness of digital marketing initiatives, personalizing marketing campaigns, increasing customer engagement, improving understanding of consumer behavior, and making digital marketing more competitive and innovative. The findings underscore the pivotal role of IoT in revolutionizing the digital marketing landscape, offering a new paradigm for businesses to navigate. However, the study also reveals the challenges faced by managers, including data security and privacy concerns, operational complexities, financial investment, workforce upskilling, and the lack of standardized protocols. As businesses seek to adapt and thrive in the digital age, understanding and addressing these challenges becomes paramount. This research provides valuable insights into the evolving relationship between IoT and digital marketing, paving the way for further exploration and practical applications in this dynamic field.